Analysing the Influence of High Transient Current Flow on White Etching Cracks in Roller Element Bearings - Potrykus, Felix; Pircher, Thomas; Wensing, Michael; Schlücker, Eberhard (International Tribology Conference, 2023)
A test rig allows the loading of deep groove ball bearings with critical conditions with regard to the formation of white etching cracks: the mechanical load, lubricant addition and current can be adjusted. High-frequency recording of the voltage drop across the test bearings reveals an information content in the signal that allows statements to be made about the occurrence of white etching cracks. Further analysis of the test bench data suggest a correlation between the bearing state and operating conditions on the morphology of the voiltage drop across the bearing contact. <br
Keywords: Bearing Failure; Bearing Fatigue; White Etching Crack; Voltage Measurement

A novel machine learning-based approach for the detection and analysis of spontaneous synaptic currents - Pircher, Thomas; Pircher, Bianca; Feigenspan, Andreas (PLoS ONE, 2022)
Spontaneous synaptic activity is a hallmark of biological neural networks. A thorough description of these synaptic signals is essential for understanding neurotransmitter release and the generation of a postsynaptic response. However, the complexity of synaptic current trajectories has either precluded an in-depth analysis or it has forced human observers to resort to manual or semi-automated approaches based on subjective amplitude and area threshold settings. Both procedures are time-consuming, error-prone and likely affected by human bias. Here, we present three complimentary methods for a fully automated analysis of spontaneous excitatory postsynaptic currents measured in major cell types of the mouse retina and in a primary culture of mouse auditory cortex. Two approaches rely on classical threshold methods, while the third represents a novel machine learning-based algorithm. Comparison with frequently used existing methods demonstrates the suitability of our algorithms for an unbiased and efficient analysis of synaptic signals in the central nervous system.
CRIS-Team Scopus Importer:2022-10-07

The structure dilemma in biological and artificial neural networks - Pircher, Thomas; Pircher, Bianca; Schlücker, Eberhard; Feigenspan, Andreas (Scientific Reports, 2021)
Brain research up to date has revealed that structure and function are highly related. Thus, for example, studies have repeatedly shown that the brains of patients suffering from schizophrenia or other diseases have a different connectome compared to healthy people. Apart from stochastic processes, however, an inherent logic describing how neurons connect to each other has not yet been identified. We revisited this structural dilemma by comparing and analyzing artificial and biological-based neural networks. Namely, we used feed-forward and recurrent artificial neural networks as well as networks based on the structure of the micro-connectome of C. elegans and of the human macro-connectome. We trained these diverse networks, which markedly differ in their architecture, initialization and pruning technique, and we found remarkable parallels between biological-based and artificial neural networks, as we were additionally able to show that the dilemma is also present in artificial neural networks. Our findings show that structure contains all the information, but that this structure is not exclusive. Indeed, the same structure was able to solve completely different problems with only minimal adjustments. We particularly put interest on the influence of weights and the neuron offset value, as they show a different adaption behaviour. Our findings open up new questions in the fields of artificial and biological information processing research.
CRIS-Team WoS Importer:2021-04-02

Wasserstoff in der Metropolregion Nürnberg – Analyse der Kompetenzen, Chancen und Herausforderungen - Pircher, Thomas; Bazan, Peter; Elhaus, Nora; Fellerer, Jonathan; German, Reinhard; Karl, Jürgen; Kolb, Sebastian; Kunz, Thomas; Opferkuch, Frank; Pilz-Lansley, Alexander; Reichenwallner, Simon; Ronge, Karlheinz; et al. (2023)
The study shows that the metropolitan region has economic potential in the product-related value chain. Depending on the scenario, this market sector can become a decisive factor and will create jobs in several fields in the European Metropolitan Region Nuremberg (EMN). However, the simulations show that the generation potential from energy surpluses is not sufficient for significant export. However, the own production of hydrogen in the metropolitan region could cover the own demand, mainly heavy duty vehicles and process heat, and thus could also be an incentive for the own infrastructure development. However, the simulation clearly shows that a pushed expansion of renewable energies is indispensable and that the storage capacities and concepts planned so far will not be sufficient to buffer the surplus energy peaks and make them available. There is a need for research and action here, both specifically for the EMN and for other regions. From our point of view, it will be crucial for the EMN that the existing industry in the EMN acquires the competences to develop and produce components, partial and complete systems for hydrogen technology. For this purpose, it is important to provide easy access to this knowledge in the form of a central knowledge center and to ensure close networking of the various players in the product-related value chai
Keywords: hydrogen; european metropolitan area; mobility; sector coupling